Brain electromagnetic activity and lightning: potentially congruent scale-invariant quantitative properties - Persinger, Michael A. (Frontiers in Integrative Neuroscience, 2012)
The space-time characteristics of the axonal action potential are remarkably similar to the scaled equivalents of lightning. The energy and current densities from these transients within their respective volumes or cross-sectional areas are the same order of magnitude. Length-velocity ratios and temporal durations are nearly identical. Careful, quantitative examination of the characteristics of lightning may reveal analogous features of the action potential that could lead to a more accurate understanding of these powerful correlates of neurocognitive processes.